Coronary stenosis risk analysis following Hodgkin lymphoma radiotherapy: A study based on patient specific artery segments dose calculation. Issue 3 (December 2015) - Moignier, Alexandra; Broggio, David; Derreumaux, Sylvie; Beaudré, Anne; Girinsky, Théodore; Paul, Jean-François; Drubay, Damien; Lefkopoulos, Dimitrios; Franck, Didier; Aubert, Bernard; Deutsch, Eric; Bourhis, Jean
Abstract: Background and purpose: The dose effect-effect relationship for cardiac diseases following radiotherapy suffers from uncertainties. Three dimensional coronary artery (CA) dose calculation after mediastinal Hodgkin lymphoma radiotherapy was performed, using the patient's coronary CT angiography (CCTA), and the relationship between the coronary arteries' radiation doses and the risk of stenosis was estimated. Materials and methods: Radiotherapy simulation CT scans and CCTAs of patients treated for a mediastinal Hodgkin lymphoma were used to merge thoracic and detailed cardiovascular anatomies. Radiation treatment parameters were used to estimate CA radiation doses. Twenty-one patients without coronary stenosis (controls) were matched with twelve patients with stenosis (cases). CA segments were considered as sub-volumes of interest. Radiation doses to stenotic segments were compared with those received by normal segments (from cases and controls) using a logistic regression. Results: In eleven cases out of twelve, the highest of the coronary dose distribution was on a damaged segment. Logistic regression with CA segments yielded an odds ratio associated with the risk of coronary stenosis of 1.049 per additional gray with the CA segment median dose (95% confidence interval, 1.004–1.095; p-value <0.05). Conclusion: The CA segment dose significantly increased the risk of stenosis on the segment. Such personalized CA dose calculations on larger cohorts are expected to improve the understanding of the cardiovascular radiation dose–effect relationship.